Noise trauma induced plastic changes in brain regions outside the classical auditory pathway. (19th February 2016) - Chen, G.-D.; Sheppard, A.; Salvi, R.
Graphical abstract: Highlights: High-frequency noise trauma induces hypoactivity at high-frequencies but hyperactivity at low-frequencies. A severe injury induces hypoactivity not only at the high-frequencies but also at the edge-frequency. A moderate injury induces hypoactivity at the high-frequencies but not at the edge-frequency. A minor injury, in contrast, induces hyperactivity at the edge-frequency but not at the low-frequency. The noise-induced hyperactivity occurs in the auditory cortex and lateral amygdala but not in striatum. Abstract: The effects of intense noise exposure on the classical auditory pathway have been extensively investigated; however, little is known about the effects of noise-induced hearing loss on non-classical auditory areas in the brain such as the lateral amygdala (LA) and striatum (Str). To address this issue, we compared the noise-induced changes in spontaneous and tone-evoked responses from multiunit clusters (MUC) in the LA and Str with those seen in auditory cortex (AC) in rats. High-frequency octave band noise (10–20 kHz) and narrow band noise (16–20 kHz) induced permanent threshold shifts at high-frequencies within and above the noise band but not at low frequencies. While the noise trauma significantly elevated spontaneous discharge rate (SR) in the AC, SRs in the LA and Str were only slightly increased across all frequencies. The high-frequency noise trauma affected tone-evoked firing rates in frequency and time-dependent manner and the changes appeared to be related to the severity of noise trauma. In the LA, tone-evoked firing rates were reduced at the high-frequencies (trauma area) whereas firing rates were enhanced at the low-frequencies or at the edge-frequency dependent on severity of hearing loss at the high frequencies. The firing rate temporal profile changed from a broad plateau to one sharp, delayed peak. In the AC, tone-evoked firing rates were depressed at high frequencies and enhanced at the low frequencies while the firing rate temporal profiles became substantially broader. In contrast, firing rates in the Str were generally decreased and firing rate temporal profiles become more phasic and less prolonged. The altered firing rate and pattern at low frequencies induced by high-frequency hearing loss could have perceptual consequences. The tone-evoked hyperactivity in low-frequency MUC could manifest as hyperacusis whereas the discharge pattern changes could affect temporal resolution and integration.